Identification and Association of Polymorphisms in the Interleukin-13 Gene with Asthma and Atopy in a Dutch Population - Howard, Timothy D; Whittaker, Paul A; Zaiman, Ari L; Koppelman, Gerard H; Xu, Jianfeng; Hanley, Marcus T; Meyers, Deborah A; Postma, Dirkje S; Bleecker, Eugene R (American journal of respiratory cell and molecular biology, 2001)
Asthma and atopy are related conditions that may share similar genetic susceptibility. Linkage studies have identified a region on chromosome 5q that contains biologic candidates for both asthma and atopy phenotypes, including several proinflammatory cytokines. Interleukin (IL)-13, one of the candidate genes in the region, is directly involved in the regulation of immunoglobulin E and has been associated with both asthma and atopy. We sought to identify new polymorphisms in the IL-13 gene, and evaluated the involvement of a subset of these variants in asthma and atopy in a case-control study using probands and spouses from a Dutch asthma family study. IL-13 was sequenced in 20 probands and 20 unaffected spouses, and 10 polymorphisms were identified, four novel and six previously reported. Three single nucleotide (nt) polymorphisms (SNPs) were detected in the 5'-promoter region, two in intron 1, and five in exon 4. Only one of the exon 4 SNPs resulted in an amino-acid change (Arg130Gln). We analyzed three SNPs in IL-13 in an extended group of 184 probands and their spouses: one in the promoter region (-1111), the Arg130Gln (nt position 4257), and a 3' untranslated region SNP (nt position 4738). The most significant associations were observed to asthma (P = 0.005), bronchial hyperresponsiveness (P = 0.003), and skin-test responsiveness (P = 0.03) with the -1111 promoter. These results provide evidence that variation in the IL-13 gene is involved in the pathogenesis of asthma and atopy. Further investigation is required to determine which specific alleles or combination of alleles contribute to these phenotypes, and the possible downstream effects of the resulting change in IL-13 levels or activity.